2022
DOI: 10.1007/s00520-022-07437-0
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of older women with early breast cancer on telemedicine during post-primary treatment

Abstract: Purpose Telemedicine has the potential to lessen healthcare burden of older patients due to frequent appointments, physical disabilities, and reliance on caretakers. To benefit from telemedicine, patients must have the capacity and willingness to engage with technology. This study aimed to better understand the telemedicine experiences of older women with nonmetastatic breast cancer regarding visit convenience, completeness, and interpersonal satisfaction. Methods Semi-structured interviews were conducted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…An evident trend that emerged from the literature included the crucial benefits from a face-to-face visit. Older adults preferred telemedicine for basic health concerns; however, face to face visits were preferred for physical exams and more serious/complex issues including hearing bad news [27 ▪ ,28]. Telemedicine is a form of communication that can be instrumental in symptom management for patients with cancer including managing pain, nausea, and vomiting [4].…”
Section: Telemedicine Modes Of Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…An evident trend that emerged from the literature included the crucial benefits from a face-to-face visit. Older adults preferred telemedicine for basic health concerns; however, face to face visits were preferred for physical exams and more serious/complex issues including hearing bad news [27 ▪ ,28]. Telemedicine is a form of communication that can be instrumental in symptom management for patients with cancer including managing pain, nausea, and vomiting [4].…”
Section: Telemedicine Modes Of Communicationmentioning
confidence: 99%
“…A group of primary care physicians and geriatricians found that proper training of older adults and clinicians was vital to the success of telemedicine [32]. Responses of older adults with breast cancer interviews included a need for training before their initial appointment would be beneficial to improve telemedicine [28]. Practice recommendations from CARG for telemedicine included education and coordination of technology platforms for older adults with cancer and caregivers [12].…”
Section: Older Adults and The Use Of Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptability of telemedicine among BC patients is also depended on the phase relative to primary treatment. Indeed, in the primary treatment phase and directly after, patients preferred full physical exam to telemedicine due to fear of recurrence [ 50 ]. Although most of responders in their study were satisfied with E-TFU, Merz et al [ 33 ] report that only 43.8% of BC survivors would like to have E-TFU after the pandemic.…”
Section: Telemedicine and Bc Beyond Covid-19mentioning
confidence: 99%
“…Indeed, with the ageing of the population, telemedicine should also adapt itself to older women with hearing and vision loss. The use of large computer screens instead of smartphones for a better perception of body language, as well as the help of patients support system for oral communication, are potential solutions for adults with sensory difficulties [ 50 ]. Racial inequalities were also reported, where Asian and non-Hispanic white women were more likely to use telemedicine than Black and Hispanic women [ 53 ].…”
Section: Telemedicine and Bc Beyond Covid-19mentioning
confidence: 99%